2021
DOI: 10.1111/ans.16591
|View full text |Cite
|
Sign up to set email alerts
|

Low‐flow vascular malformations of the hand and forearm: a multidisciplinary experience in a tertiary paediatric centre

Abstract: Background: Vascular malformations (VMs) involving the hand and forearm in children provide management challenges due to complex anatomy, indispensable functionality and developmental implications. Methods: The institution's Vascular Registry was searched for patients with hand and arm VMs, supplemented by chart review of included patients.Results: Twenty-one patients were identified, 52% male, with mean presenting age 5.2 years. Venous malformations predominated (71%), followed by lymphatic-venous (19%), lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies on treatment outcomes of sclerotherapy/embolization often focus on a specific CVM subtype, a specific anatomical location, or a specific agent, and the definition of a successful treatment outcome varies, all of which limits comparability. In recent studies on pediatric patients, a complete response was reported in 11-89% of the patients and improvement in 57-100% [34,48,49,51,54,69,70]. In LMs, bleomycin seems to be the most effective agent, and macrocystic lesions often showed a better response than microcystic and/or mixed lesions [49,53,70].…”
Section: Sclerotherapy/embolizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on treatment outcomes of sclerotherapy/embolization often focus on a specific CVM subtype, a specific anatomical location, or a specific agent, and the definition of a successful treatment outcome varies, all of which limits comparability. In recent studies on pediatric patients, a complete response was reported in 11-89% of the patients and improvement in 57-100% [34,48,49,51,54,69,70]. In LMs, bleomycin seems to be the most effective agent, and macrocystic lesions often showed a better response than microcystic and/or mixed lesions [49,53,70].…”
Section: Sclerotherapy/embolizationmentioning
confidence: 98%
“…Cosmetic camouflage may be used to improve the appearance [33]. Compression garments can reduce symptoms and possibly prevent lesion-related complications [34]. Conservative approaches also include proper skin, wound and ulcer care.…”
Section: Treatment 61 Conservativementioning
confidence: 99%
See 1 more Smart Citation
“…Venous malformation, defined as a low-flow lesion among vascular anomalies, is the most common form of congenital vascular malformation, which accounts for more than 50% of all vascular malformations, with a prevalence of around 1% [ 1 , 2 , 3 , 4 ]. Formed at birth, venous malformations grow with age and might lead to pain, edema or compression on the surrounding structures, which can lead to a reduced quality of life and the requirement of repetitive medical treatments in order to relieve the discomfort [ 2 , 5 ]. Despite the fact that medical compression stockings are commonly provided as a noninvasive therapy to relieve symptoms of venous and lymphatic disorders, prospective studies verifying the benefit of medical compression therapy in venous malformations are lacking [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%